Cash lfow analysis of river cargo ship projected for possibility of pushing towage - Novomeská, Jana; Patek, Peter (Communications - Scientific letters of the University of Zilina, 1999)
This work deals with river cargo ship analysis of effectiveness relating to technical parameters of single navigation and in configuration with barges DE. Input comes from the propulsion conception for reachable speeds for ACF of the ship analysis during the ordering for a specific relation. Evaluated are results of rate of turnover and final ACF of the vessel, as well as analyses of a group of vessels by specific freight rates independent of the building price of the ship.